IMPLEMENTASI METODE ON-PAGE SEO UNTUK MENINGKATKAN TRAFIK PENGUNJUNG PADA WEBSITE WARALABAKITA - William Chandra; Sudirman; Renny (KHARISMA Tech, 2023)
WaralabaKita is a website that acts as a portal or web service to help franchisees find information about franchises. Due to the website does not appear on search engines, causing lack of visitors on the website, it is necessary to implement on-page SEO practices in order to overcome these problems. The first step before implementing on-page SEO practices is determining keywords, then implementing common on-page SEO practices which includes optimizing title element, implementing meta keywords, meta descriptions, optimizing heading elements, and using alt and title attributes on image elements. After the implementation of on-page SEO on WaralabaKita website, results showed an insignificant increase in visitor traffic, based on the data collected in Google Analytics & Search Console, the data showed a decrease in traffic after an increase in the amount of traffic. Based on the results of this research on implementing 5 common on page SEO practices, is not effective in increasing the amount of traffic.